The 2008 SWS surveys of enterprises on corruption - Social Weather Stations (Institute). (Quezon City Social Weather Stations, 2004)
Result of surveys conducted by Social Weather Stations on public sector corruption in Philippines, 2000-2004.
Title from disc label.
Production level cataloging.
Text (presentation in PPT format).
Keywords: Political corruption -- Philippines; Public institutions -- Corrupt practices -- Philippines